2006
DOI: 10.2174/138920006778520570
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Flavonoids to Influence Drug Metabolism and Pharmacokinetics by Local Gastrointestinal Mechanisms

Abstract: In recent years, public and scientific interest in plant flavonoids has tremendously increased due to postulated health benefits. Whereas the amount of flavonoids ingested with the regular diet is rather low, the use of supplements enriched with these polyphenolics is becoming increasingly popular. This raises concerns about possible interactions of flavonoids with therapeutic drugs, because both are xenobiotics and, thus, share at least partially the same metabolic pathways. A number of in vitro studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 168 publications
(243 reference statements)
1
78
0
2
Order By: Relevance
“…gov.cn/datasearch/face3/dir.html). Although most flavonoids are rapidly metabolized in the intestinal mucosa and the liver, and the bioavailability of flavonoids and their metabolites is generally low, with peak values of plasma concentration in the low micromolar range (Manach et al, 2005;Cermak and Wolffram, 2006), some clinical studies have demonstrated that flavonoids can affect the metabolism of other drugs (Peng et al, 2003;Rajnarayana et al, 2003;Choi et al, 2004). In the current investigation of the inhibition of CYP2C9-mediated diclofenac 4Ј-hydroxylation, we have shown that many flavonoids are potent inhibitors of CYP2C9, with K i values Յ2.2 M, and, for galangin, as low as 0.15 M. These findings raise concerns about possible drug interactions between flavonoids and the some 100 therapeutic drugs metabolized by CYP2C9 (Kirchheiner and Brockmöller, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…gov.cn/datasearch/face3/dir.html). Although most flavonoids are rapidly metabolized in the intestinal mucosa and the liver, and the bioavailability of flavonoids and their metabolites is generally low, with peak values of plasma concentration in the low micromolar range (Manach et al, 2005;Cermak and Wolffram, 2006), some clinical studies have demonstrated that flavonoids can affect the metabolism of other drugs (Peng et al, 2003;Rajnarayana et al, 2003;Choi et al, 2004). In the current investigation of the inhibition of CYP2C9-mediated diclofenac 4Ј-hydroxylation, we have shown that many flavonoids are potent inhibitors of CYP2C9, with K i values Յ2.2 M, and, for galangin, as low as 0.15 M. These findings raise concerns about possible drug interactions between flavonoids and the some 100 therapeutic drugs metabolized by CYP2C9 (Kirchheiner and Brockmöller, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, the ability of flavonoids to inhibit isoforms of CYP450, particularly CYP1A1 and CYP1A2, has been extensively confirmed (Cermak and Wolffram, 2006). Several clinical studies have reported that some flavonoids have the capacity to alter drug metabolism in vivo (Peng et al, 2003;Rajnarayana et al, 2003;Choi et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Many flavonoids are substrates of the most pharmacologically relevant ABC transporters, P glycoprotein/ MDR1, MRP, and BCRP [123] [124] but so far scientific effort has focused on the modulation of the transporter by flavonoids [125]. Whereas some flavonoids were shown to inhibit MDR1-mediated transport processes by directly interacting with the vicinal ATP-and steroid-binding sites [126], others (like (-) epicatechin from green tea) were shown to activate MDR1 by a heterotropic allosteric mechanism [127].…”
Section: Flavonoidsmentioning
confidence: 99%
“…For example, the oral bioavailability of biochanin A was increased approximately 2-fold when coadministered with the BCRP inhibitors quercetin and epigallocatechin-3-gallate (EGCG) in rats (Moon & Morris, 2007). However this effect may at least partially be due to inhibition of metabolizing enzymes, as there is evidence that both quercetin and the green tea polyphenols may inhibit both Phase 1 and 2 metabolism (Cermak & Wolffram, 2006). Kaempferol has also been reported to increase quercetin permeability across MDCKII-Bcrp monolayers by inhibition of Bcrpmediated quercetin efflux .…”
Section: Absorption From Gastrointestinal (Gi) Tractmentioning
confidence: 99%